2012
DOI: 10.3168/jds.2012-5439
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of the flavonol quercetin in cows after intraruminal application of quercetin aglycone and rutin

Abstract: The bioavailability of quercetin has been intensively investigated in monogastric species, but knowledge about its bioavailability in ruminants does not exist. Thus, the aim of the present study was to determine the bioavailability of quercetin in nonlactating cows equipped with indwelling catheters placed in one jugular vein after intraruminal and additionally after i.v. application, respectively. Quercetin was administered intraruminally in equimolar amounts, either in the aglycone form or as its glucorhamno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
86
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(97 citation statements)
references
References 37 publications
10
86
0
1
Order By: Relevance
“…Olthof et al [15] , 2000 Human Pure compound Isoquercitin -37 ± 12 1110 ± 48 Chang et al [17] , 2005 Rat Pure compound Isoquercitin -10 -Lesser et al [18] , 2006 Pig Standard diet Quercitin (standard) ± 30 95 -Quercitin (high fat content) 65 Lan et al [19] , 2007 Rat Pure compound Quercitin -114-294 -Krogholm et al [20] , 2010 Human "Juice mix" Quercitin -216 ± 96 -Berger et al [21] , 2012 Cow Standard diet Quercitin -30.0 ± 0.0 -Gohlke et al [22] , Orfali GC et al . Isoquercitrin in cancer above 25 µg/mL, stimulated cell proliferation and cellular metabolism by increasing mitochondrial activity.…”
Section: First Maximummentioning
confidence: 99%
“…Olthof et al [15] , 2000 Human Pure compound Isoquercitin -37 ± 12 1110 ± 48 Chang et al [17] , 2005 Rat Pure compound Isoquercitin -10 -Lesser et al [18] , 2006 Pig Standard diet Quercitin (standard) ± 30 95 -Quercitin (high fat content) 65 Lan et al [19] , 2007 Rat Pure compound Quercitin -114-294 -Krogholm et al [20] , 2010 Human "Juice mix" Quercitin -216 ± 96 -Berger et al [21] , 2012 Cow Standard diet Quercitin -30.0 ± 0.0 -Gohlke et al [22] , Orfali GC et al . Isoquercitrin in cancer above 25 µg/mL, stimulated cell proliferation and cellular metabolism by increasing mitochondrial activity.…”
Section: First Maximummentioning
confidence: 99%
“…One of spotlight herbal phenolic substances is quercetin, which is found in many edible plants, fruits and vegetables (Erlund, 2004;Formica et al, 1995). The bioavailability studies of quercetin and its metabolites; aglycone and rutin, in cows demonstrated that quercetin can be absorbed via digestive tracts and eventually entered the plasma (Berger et al, 2012;Gohlke et al, 2013;Maciej et al, 2015). Several in vivo studies of quercetin in neonatal calves, periparturient and lactating cows, in the aspects of bovine health and production, have been recently reported (Gohlke et al, 2013;Maciej et al, 2015;Stoldt et al, 2015); however, another point of view remains scarce in bovine innate immunity.…”
Section: Introductionmentioning
confidence: 99%
“…However, quercetin in the form of aglycon is always the main metabolite found in plasma (Berger et al, 2012). Unfortunately, there are no records describing flavonoids' bioavailability in the case of chronic, multiple treatment and only this data could reflect the physiological situation when cows are continuously exposed to bioflavonoids present in pasture.…”
mentioning
confidence: 99%
“…example the absolute bioavailability of flavonols after single intraruminal application amounts to 0.1% and 0.5% for quercetin aglycon and rutin (quercetin glycoside), respectively (Berger et al, 2012). However, quercetin in the form of aglycon is always the main metabolite found in plasma (Berger et al, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation